Structural Estimation of Search Intensity: Do Non-Employed Workers Search Enough? - Pieter A. Gautier; Jose Luis Moraga-Gonzalez; Ronald P. Wolthoff (Tinbergen Institute, 2007)
We present a structural framework for the evaluation of public policies intended to increase job search intensity. Most of the literature defines search intensity as a scalar that influences the arrival rate of job offers; here we treat it as the number of job applications that workers send out. The wage distribution and job search intensities are simultaneously determined in market equilibrium. We structurally estimate the search cost distribution, the implied matching probabilities, the productivity of a match, and the flow value of non-labor market time; the estimates are then used to derive the socially optimal distribution of job search intensities. From a social point of view, too few workers participate in the labor market while some unemployed search too much. The low participation rate reflects a standard hold-up problem and the excess number of applications result is due to rent seeking behavior. Sizable welfare gains (15% to 20%) can be realized by simultaneously opening more vacancies and increasing participation. A modest binding minimum wage or conditioning UI benefits on applying for at least one job per period, increases welfare.
Keywords: J64; J31; J21; E24; C14; 330; job search; search costs; labor market frictions; wage dispersion; welfare; structural estimation; Arbeitslosigkeit; Arbeitsnachfrage; Arbeitsuche; Informationskosten; Wohlfahrtsanalyse; Theorie; Niederlande